Implementasi Demokrasi Deliberatif Dalam Formulasi Kebijakan Bantuan Dana Kesehatan Desa Trayu - Ningtyas, Dhini Wahyu; Mutmainah, Mutmainah; Mudawamah, Mufidatul; Maulia, Fazza Nikmatul (Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to examine the implementation of deliberative democracy in the policy formulation process of the health fund assistance program in Trayu Village, Kendal Regency. The research is driven by the low level of community participation in village deliberations, despite the normative expectation that public policies should be formulated in a participatory manner to reflect the aspirations of the people. A qualitative approach was employed, using in-depth interviews with village officials, BPD and residents from various social backgrouds. The findings reveal that the health fund policy, which has been implemented since 2024, still follows a top-down pattern in which decisions are often dominated by village elites without the direct involvement of the most affected community groups. Village deliberation forums, which ideally serve as aspirational spaces, function instead as formal arenas for ratifying decisions previously drafted by village authorities and the BPD. Discussions remain confined to certain circles, and the broader community’s aspirations are generally no channeled through formal mechanisms. These findings highlight the need to improve the deliberation process by making it more inclusive-such as integrating informal social spaces (women’s groups, neighbourhood patrols, religious gathering) as avenues for capturing public input, and leveraging information technology to expand citizen participation. The implications underscore that deliberative democracy at the village level has not yet been optimally implemented and requires substantial reform so that village policies genuinely reflect the wider community’s needs. A shift from a top-down to a bottom-up paradigm is essential to ensure justice, transparency, and sustainability in village governance.